POTENSI REVITALISASI TRANSPORTASI SUNGAI DI PROVINSI LAMPUNG - R. Didin Kusdian (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2011)
The river provides a natural potential as a medium of movement for water vehicles such as boat or ship. Especially for the transport of goods, the revitalization of river transport can play an important role in load reduction in land transport by truck, so as to reduce the acceleration of road damage caused by truck traffic loads. To implement the river transport revitalization in the Province of Lampung, it is required the design and production of ships that have special characteristics that are suitable for a wide but shallow river.Key words: river transportation, load of land transportation, road damage, ship design.